Achieving thermally stable and anti-hydrolytic Sr2Si5N8:Eu2+ phosphor via a nanoscale carbon deposition strategy. Issue 3 (1st February 2021) - Liu, Yunxia; Wang, Hui; Chen, Daiyan; Gao, Lin; Wang, Xin; Jian, Xian; Mu, Chunhong; Xu, Xin; Zhao, Yujie; Yin, Liangjun
Abstract: Chemical stability of phosphors is critical to the efficiency and lifetime of the white light-emitting diodes. Therefore, many strategies have been adopted to improve the stability of phosphors. However, it is still lack of report on the improvement of thermal stability and hydrolysis resistance of phosphors by a single layer coating. Due to the high transmittance and high chemical inertness of graphene, it was coated on the surface of Sr2 Si5 N8 :Eu 2+ phosphor by chemical vapor deposition, aiming to improve its thermal stability and hydrolysis resistance. The chemical composition and microstructure of the coating were characterized and analyzed. A nanoscale carbon layer was attached on the surface of Sr2 Si5 N8 :Eu 2+ phosphor particles in an amorphous state. In coated Sr2 Si5 N8 :Eu 2+ phosphor, the oxidation degree of Eu 2+ to Eu 3+ was significantly suppressed. At the same time, the surface of Sr2 Si5 N8 :Eu 2+ particle turned from hydrophilic to hydrophobic after carbon coating, and consequently the hydrolysis resistance of Sr2 Si5 N8 :Eu 2+ phosphor was greatly improved. After tests at 85 °C and 85% humidity for 200 h, the carbon coated Sr2 Si5 N8 :Eu 2+ phosphor still maintained about 95% of its initial luminous intensity as compared with 35% of the uncoated. By observing the in-situ microstructure evolution of coated phosphor in air-water vapor environment, remained presence of the carbon layer even at 500 °C explained the excellent chemical stability of carbon coated Sr2 Si5 N8 :Eu 2+ phosphor in complex environment. These results indicate that a nanoscale carbon layer can be used to provide superior thermal stability and hydrolysis resistance of (oxy) nitrides phosphors.